An investigation of teachers' written feedback practices at different proficiency levels: An Egyptian perspective - Soliman, Noura Nabil (AUC Knowledge Fountain, 2016)
There have been ongoing investigations on whether providing written corrective feedback on students' errors in L2 writing is effective in improving their writing skills. Research has focused mainly on the effectiveness of different feedback techniques, students' preferences and perception, and teachers' beliefs and practices regarding written corrective feedback. However, limited research has investigated teacher feedback practices at different levels of students' proficiency. This study investigated teacher feedback practices at two different proficiency levels in an English-medium university in Cairo, Egypt. The study adopted a mixed-methods data collection approach, where data were gathered by interviewing five English as a Foreign Language (EFL) instructors and collecting 95 written feedback samples from them, which demonstrated their written feedback practices at the different levels. Written feedback samples were analyzed in terms of the feedback strategies used by teachers at high and low proficiency levels as well as the focus of written corrective feedback employed at both levels. Follow up interviews with five instructors were conducted to better understand whether teachers adapt their written feedback according to the proficiency level of their students and to see if there were other factors that affect their feedback practices at the different levels. The results indicated that there were differences between the written feedback provided at high and low proficiency levels. Analyzing the written feedback samples revealed that teachers tended to use more direct feedback at the lower proficiency level by indicating the errors and correcting them for students, with the feedback focusing more on language-related issues. In contrast, indirect coded feedback was more frequently used at the higher proficiency level, as teachers tended to categorize the error without correcting it, focusing more on content, idea development, and integration of sources. Moreover, the interview data showed that three teachers stated that they prefer direct feedback with the lower levels because it may take a long time for students to understand coded feedback, especially at the beginning of a semester. However, two teachers reported that they prefer using indirect feedback with both high and low-proficiency students in order to encourage them to become more autonomous and independent. In terms of the factors that affect teachers' feedback practices, the findings showed that the outcomes and requirements of the program taught as well as whether written feedback is handwritten or provided online have a great effect on teacher feedback practices at the different levels. The study concluded that different feedback strategies could be employed at low proficiency levels in order to help students become more independent, and that teachers could determine their feedback practices based on what is best for students' L2 improvement.